Severe Maternal Morbidity in a Large Cohort of Women With Acute Severe Intrapartum Hypertension. Issue 2 (June 2017) - Kilpatrick, S.J.; Abreo, A.; Greene, N.; Melsop, K.; Peterson, N.; Shields, L.E.; Main, E.K.
Abstract : ( Am J Obstet Gynecol . 2016;215(1):91.e1–91.e7) Adverse effects of hypertensive disorders of pregnancy such as stroke, eclampsia, hemolysis, elevated liver enzymes, low platelet count syndrome, renal failure, and disseminated intravascular coagulation are commonly associated with high rates of maternal morbidity and mortality in the United States. The present study aimed to analyze existing management patterns in a large group of women with severe intrapartum hypertension, to determine the maternal morbidity associated with severe intrapartum hypertension and compare it to that in women without severe hypertension.